INTEGRASI KONTRAK TERAPEUTIK DAN PERLINDUNGAN KONSUMEN DALAM LAYANAN MEDIS - Yatini, Yatini (Jurnal Supremasi, 2025)
The legal relationship between doctors and patients in medical practice is not merely ethical in nature but also establishes a contractual bond known as a therapeutic contract. Within the framework of civil law, this contract fulfills the elements of an agreement as regulated in Articles 1313 and 1320 of the Indonesian Civil Code. Patients, as recipients of medical services, can be classified as consumers as defined under Law Number 8 of 1999 on Consumer Protection (UUPK). This study aims to analyze the construction of therapeutic contracts as service agreements in civil law, examine the legal status of patients as consumers, and formulate a model for strengthening legal protection for patients in healthcare services. The research employs a normative juridical method with statutory, conceptual, and case study approaches. The findings indicate that although therapeutic contracts are valid under civil law, in practice they still generate imbalances in the doctor–patient relationship, particularly in terms of information and medical decision-making. This research proposes an integrative model of legal protection through written medical contracts, harmonization of regulations between the Health Law and UUPK, expansion of the authority of the Consumer Dispute Settlement Body (BPSK), and enhancement of patients’ legal literacy. This model is expected to foster a more balanced and just legal relationship in healthcare services.